Mathematical Model of Available Control of Dredger Movement (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The article highlights the scientific and technical issue related to the optimal placement of dredgers on the damless section of the Amudarya and in the channel for supplying water to the I-РS in order to optimize their operation on the river and canal sections. In turn, the question of the optimal location of dredgers gives rise to the need to study the dynamics of the relief of the riverbed or canal.